Effects of colchicine, interferon β, IVIG, tocilizumab and corticosteroids on COVID-19 patient survival from all presently available published clinical trials: A narrative review - Kobra Bahrampour Juybari; Manzume Shamsi meymandi; Hamideh Bashiri (Caspian Journal of Internal Medicine)
One of the deadliest diseases in the world, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the ongoing global pandemic known as COVID-19. COVID-19 symptoms range from undetectable to deadly, hyper-inflammatory response and the overproduction of pro-inflammatory cytokines or hypercytokinemia are key factors in the pathophysiology of severe COVID-19. However, no specific and effective treatment was available, anti-inflammatory drugs have been vastly used for treating patients. The goal of this narrative literature review (2020–2022) was to elucidate the connection between anti-inflammatory medications and COVID-19 outcomes, such as safety and survival rate. Overall, these studies are consistent in presenting that anti-inflammatory drug can be advised to target the host immune response in patients and have been beneficial in reducing the mortality rate. This is revealed in current recommendations from prominent global public health authorities, which support anti-inflammatory drug use for a decrease of cytokine storm during COVID-19.